(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
The purpose of this article is to use effective forms, methods and means of disseminating information about professions among secondary school students, taking into account their personal capabilities, working on the basis of a technological approach in this process, which guarantees finding a positive solution to the problem. It is also aimed at improving the model of the pedagogical process aimed at consciously choosing a profession in students.